EFEKTIVITAS PENERAPAN METODE SOROGAN DALAM MEMAHAMI KITAB KUNING: EFEKTIVITAS PENERAPAN METODE SOROGAN DALAM MEMAHAMI KITAB KUNING - Rahmaniah; basri mahmud; Sudirman (Jurnal Ilmiah Tarbiyah Umat, 2024)
This study aims to evaluate the performance of the Sorogan method in understanding the Kitab Kuning at Pondok Pesantren Salafiayah Parappe, located in Campalagian District, Polewali Mandar Regency. The Sorogan method, which involves students learning directly in front of a teacher, has proven to be effective in helping students understand classical texts, Arabic language, tafsir, fiqh, and hadith. This research uses a qualitative approach with a case study, collecting data through interviews, observations, and document analysis. The findings indicate that this method accelerates students' understanding of the Kitab Kuning due to the direct interaction between students and teachers. However, challenges such as heavy academic workloads, differences in students' abilities, and limited numbers of teachers are present. Despite these challenges, the Sorogan method has proven effective in enhancing students' understanding at this pesantren.